Safety and efficacy of convalescent plasma for COVID-19: the preliminary results of a clinical trial - Vladimir P. Baklaushev; Alexander V. Averyanov; Anna G. Sotnikova; Anastasia S. Perkina; Alexander V. Ivanov; Gaukhar M. Yusubalieva; Oksana N. Novikova; Valentina E. Shikina; Nikolay V. Dupik; Anna G. Kedrova; Andrey E. Sanzharov; Elena V. Shirshova; et al. (Клиническая практика, 2020)
Background. The lack of effective etiotropic therapy for COVID-19 has prompted researchers around the globe to seekr various methods of SARS-CoV-2 elimination, including the use of convalescent plasma.